Dynamics of the Simplest Piecewise Linear Discontinuous Mappings - D. S. Kaschenko (Моделирование и анализ информационных систем)
The dynamics of one-dimensional piecewise linear mapping with one rupture is investigated. In the space of parameters we defined regions with different dynamical effects.